Integrated Shock Absorber With Both Tunable Inertance and Damping - Zhong, Wei-Min; Zhu, An-Ding; Bai, Xian-Xu Frank; Wereley, Norman M.; Zhang, Nong (Frontiers in Materials, 2020)
Inerter is a two-terminal mass element, and the applied force is proportional to the relative acceleration between the terminals. According to the second class of mechanical–electrical analogy, the inerter corresponds exactly to the capacitor in the electric network. Aiming at improving the limited vibration isolation performance using the constant inertance of a conventional inerter, a new semi-active inerter based on smart material, magnetorheological (MR) fluid, is proposed in this paper. Furthermore, according to the design concept of “functional integration”, the MR inerter, an MR damper, and a spiral spring are integrated to realize a new integrated inerter-spring-damper (IISD) with both adjustable inertance and damping characteristics. The MR inerter consists of a ball screw, an MR clutch, MR fluid, excitation coils, an excitation shell, a flywheel, a flywheel shell, a connector, upper and lower covers, bearings, and seals. The tunable inertance is achieved by adjusting the excitation current in the excitation coils to change the operating state of the MR clutch. The MR damper and the spiral spring provide variable damping and constant stiffness, respectively. The mathematical model of the IISD is established. The adjustment principle of inertance is verified by numerical simulation, and the mechanical output characteristics of the IISD are analyzed. Besides that, the 1/4 vehicle suspension model based on the proposed IISD is built by using MATLAB/SimMechanics. The frequency response and the unit impulse response characteristics of the suspension are obtained via the comfort-oriented virtual experiment. The simulation results show that the suspension with the IISD has 23.0% higher performance than the conventional suspension in vehicle body acceleration, and the suspension deflection and the dynamic tire load are also improved.